Chesterton, Lewis, and the shadow of Newman: a study in method. (12th January 2023) - Pickering, David
Abstract: In this essay I argue for a line of descent, in terms of methodology as an apologist, from J.H. Newman to G.K. Chesterton, and hence to C.S. Lewis. I analyse aspects of Chesterton's methodology as an apologist which strongly suggest the influence of Newman. I then argue that Newman may have exercised a greater influence on Lewis's methodology as an apologist, through Chesterton, than has previously been realised. This raises questions for future study concerning Newman's possible influence, not only on Lewis, but on the other Inklings and related thinkers such as Dorothy Sayers.